Sustained increase in depression and anxiety among psychiatrically healthy adolescents during late stage COVID-19 pandemic - Cochran, Gabe; Cohen, Zsofia P.; Paulus, Martin P.; Tsuchiyagaito, Aki; Kirlic, Namik (Frontiers in Psychiatry, 2023)
Background Adolescents have experienced increases in anxiety, depression, and stress during the COVID-19 pandemic and may be at particular risk for suffering from long-term mental health consequences because of their unique developmental stage. This study aimed to determine if initial increases in depression and anxiety in a small sample of healthy adolescents after the onset of the COVID-19 pandemic were sustained at follow-up during a later stage of the pandemic. Methods Fifteen healthy adolescents completed self-report measures at three timepoints (pre-pandemic [T1], early pandemic [T2], and later pandemic [T3]). The sustained effect of COVID-19 on depression and anxiety was examined using linear mixed-effect analyses. An exploratory analysis was conducted to investigate the relationship between difficulties in emotion regulation during COVID-19 at T2 and increases in depression and anxiety at T3. Results The severity of depression and anxiety was significantly increased at T2 and sustained at T3 (depression: Hedges’ g [T1 to T2] = 1.04, g [T1 to T3] = 0.95; anxiety: g [T1 to T2] = 0.79, g [T1 to T3] = 0.80). This was accompanied by sustained reductions in positive affect, peer trust, and peer communication. Greater levels of difficulties in emotion regulation at T2 were related to greater symptoms of depression and anxiety at T3 (rho = 0.71 to 0.80). Conclusion Increased symptoms of depression and anxiety were sustained at the later stage of the pandemic in healthy adolescents. Replication of these findings with a larger sample size would be required to draw firm conclusions.